TINGKAT PENCAPAIAN KEMAMPUAN GURU SD DALAM MENGGUNAKAN APLIKASI ANATES MELALUI PELATIHAN - Sudarto Sudarto; Abd. Hafid; Abd. Kadir (Bajang Institute, 2023)
The partnership of Program Kemitraan (PKM) are the elementary school teachers in Bone Regency who are UNM partners through the MOU. The problem of this PKM is that the UNM partner elementary school teachers have not been able to analyze the question items using the Anates application. To overcome this problem, face-to-face training and direct guidance were carried out. The methods used in this PKM are (1) observation, (2) lecture, (3) demonstration, (4) question and answer, and (5) training. Activities are carried out in three stages, namely; (1) planning, (2) implementation, and (3) evaluation of the activities. The program planning stage includes activities: (1) preparing a guide on how to analyze the test items using Anates and (2) preparing the activity evaluation instruments. The implementation stage includes activities: (1) conducting questions and answers with teachers to find out their initial knowledge about how to analyze the question items using Anates, (2) providing the explanations to the teachers on how to analyze the question items using Anates, and (3) training the teachers on how to analyze the test items using Anates. The evaluation stage includes activities: evaluating the teacher's ability to analyze the questions using Anates. The results and conclusions of the training show that: the training activities were carried out smoothly without significant obstacles and were enthusiastically received by all participants, the participants' ability to use the Anates application was at the excellent category consists of: the ability to open applications, import the raw data, process the data, save the files, save the data, and interpret the data processing results